Rozwijanie motywacji uczniów do nauki - Cywńska, Małgorzata (Wydawnictwo Naukowe UAM, 2012)
Developing motivation to learn is extremely important for the whole process of education. Race of skills (competition), often occurring in the classroom, causes negative motivations to learn, destroys students' love of learning, and promotes the winning over others. Whereas the activities aimed at self-improvement that ensure equal opportunities for success for students by rewarding them for their curiosity, creativity and desire to seek new information, promote the induction of positive motivation to learn. Viewed as a general disposition, or permanent tendency, to see learning as something natural that brings certain cognitive benefits, or as a state in which, in any given situation, we get involved in certain activities in order to master notions and skills, learning motivation is a value that is hard to overestimate in today’s world. A central figure in developing this motivation is a teacher. Acting as both a manager and a leader, the teacher creates a learning community within a classroom that is based on mutual help, that instils a sense of security, and is conducive to success. A teacher with manager-leader qualities is one who imparts his knowledge in a clear and attractive way and employs diversified teaching strategies that involve information processing and skill acquisition. Among other things, encouraging learning motivation in children entails offering them unconditional acceptance with conditional acceptance of their behaviour, nurturing their sense of competence and effective action, and developing their self-esteem and sense of internal control.
Developing students motivation to learn
Keywords: race of skills (competition) in the classroom; motivation models; external motivation; internal motivation; motivation to learn; teacher as manager – leader; teacher as manager – boss; didactic community